The religious situation in Japan during Tokugawa dynasty (1603-1867). - Balakaeva., L. T. (Journal of Oriental Studies, 2016)
During the reign of Tokugawa Buddhism lost the role of the official ideology of the ruling circles. Tokugawa shoguns headed for the eradication of Shintoism since he was associated with the emperor. Christianity was destroyed. Konfuntsianstvo became the official ideology in interpreting Chinese philosopher Zhu Xi.